Pengaruh media pembelajaran berbasis augmented reality terhadap keterampilan berpikir tingkat tinggi matematika peserta didik kelas IV SD - Anfika Rachmansyah; Karsono Karsono; Sandra Bayu Kurniawan (Jurnal Pendidikan Dasar, 2025)
The development of learning media can be enhanced by utilizing technology, one of which is Augmented Reality (AR). AR allows students to interact directly with three-dimensional models, facilitating the understanding of abstract concepts through concrete visualization and interactive learning experiences. This study aims to determine the effectof AR-based learning media in enhancing higher-order thinking skills among fourth-grade elementary school students. A quantitative method with a quasi-experimental design was employed, with the sample divided into experimental and control groups to compare mathematics learning outcomes on the topic of geometry. The research instrument consisted of HOTS-based questions administered in pretests and posttests. The results showed a significant difference in the average posttest scores, with the experimental class achieving higher scores than the control class. The t-test using the independent sample t-test indicated a significance value of p = 0.003 < 0.05, confirming a significant difference between the experimental and control groups. Therefore, it can be concluded that AR is positively influences higher-order thinking skills, including analysis, evaluation, and creation. This technology offers an engaging and in-depth learning experience, particularly in understanding geometric concepts.